A Qualitative Exploration of U.K. Prisoners' Experiences of Substance Misuse and Mental Health Difficulties, and the Breaking Free Health and Justice Interventions. (July 2016) - Elison, Sarah; Weston, Samantha; Dugdale, Stephanie; Ward, Jonathan; Davies, Glyn
This qualitative study explored prisoners' lived experiences of substance use and mental health difficulties and aimed to examine perceived links between these two areas and how they might be associated with recovery during engagement with the Breaking Free Health and Justice (BFHJ) treatment programs. Interviews were conducted with 32 prisoners receiving treatment for substance use in North-West England. Emerging from prisoners' interviews were themes relating to difficult life experiences from childhood into adulthood, how these experiences played a role in the emergence of their multiple and complex difficulties, their treatment experiences, and how their current involvement with the criminal justice system acted as a catalyst for positive change, including engagement with the BFHJ programs. This study identified the roles of substance use and mental health difficulties in the lives of participants, identified how their multiple and complex difficulties might be addressed, and provided insights into prisoners' interpretations of their life experiences.